Answer:
see explanation
Explanation:
(a)
+
+
= 0 ( multiply through by abc to clear the fractions )
5bc + 3ac + 7ab = 0 ( subtract 5bc from both sides )
3ac + 7ab = - 5bc ( factor a out of each term on the left side )
a(3c + 7b) = - 5bc ← divide both sides by (3c + 7b)
a = -
![(5bc)/(3c+7b)](https://img.qammunity.org/2022/formulas/mathematics/high-school/af52dywdo0x37tvrxmqw51pmixn3grfgmd.png)
---------------------------------
(b)
p =
( multiply both sides by q )
pq =
← square both sides
(pq)² = 4r(q² - s) ← distribute
p²q² = 4rq² - 4rs ← subtract 4rq² from both sides
p²q² - 4rq² = - 4rs ( multiply through by - 1 )
4rq² - p²q² = 4rs ← factor out q² from each term on the left side
q²(4r - p²) = 4rs ← divide both sides by (4r - p²)
q² =
( take the square root of both sides )
q = ±
![\sqrt{(4rs)/(4r-p^2) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/j7nggrwk6vmxafw373q98pusofwve7dumo.png)